MENINGKATAN HASIL BELAJAR SERVIS BAWAH BOLA VOLI PADA SISWA MELALUI PERMAINAN VOLKAS (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to determine increase in under service of learning outcomes the volleyball in grade IVSD NegeriPangempon Kabupaten Batang. The method used in this study, the research methods classaction to be planned in two cycles to see an increase in under service of learning outcomes thevolleyball through the game volkas. Every action attempts designed to achieve the purpose in one unitas a cycle consisting of four stages, that is: action planning, action, observation and reflection for thenext planning cycle. In the learning process of the first cycle the average value increased in the learningof students 75 to 80 the second cycle. For the number of students who achieve learning completeness inthe first cycle is 11 students with learning completeness percentage reached 73%, an increase in thenumber of learning cycles II to 14 students, while for the percentage reached 93% completeness. Basedon the results of this study concluded that the application of learning through play volkas modificationsto improve learning outcomes in under service the volleyball in grade IV SD Negeri PangemponKabupaten Batang 2012/2013. Suggestions for Penjaskes teachers everywhere should be able to createan atmosphere of active learning, innovative, creative, effective, and fun for students.